Design and delivery of an innovative speech pathology service-learning program for primary school children in Far West NSW, Australia - Sue Kirby; David Lyle; Debra Jones; Claire Brunero; Alison Purcell; Pascale Dettwiller (Sax Institute, 2018)
Background: Children growing up in Australian rural communities have more communication impairments than their urban counterparts. Communication impairments, if left unresolved in school starters, lead to long-term learning and behavioural problems. Rural communities are disadvantaged by a scarcity of health professionals. Methods: Supervised speech pathology students on rural clinical placement provided speech, language and communication screening, assessment and therapy to children starting kindergarten in Broken Hill, New South Wales, Australia. The students collected service outcome data for children in the program. Results: Analysis of the outcome data demonstrated improvements in communication impairments for approximately one-quarter of the children. Conclusion: The service-learning program used in this study is designed to facilitate implementation in other locations. The model resulted in some improvement in communication impairments. It has the potential to revolutionise undergraduate student learning placements, as well as address the chronic health professional shortage in rural Australia.